Chemical composition of the essential oil of Xanthocyparis vietnamensis Farjon and Hiep from Vietnam - Thai, Tran Huy; Hiep, Nguyen Tien; Hong, Phung Tuyet; Minh, Do Thi (Academia Journal of Biology, 2014)
Chemical composition of the essential oil of Xanthocyparis vietnamensis Farjon and Hiep from Vietnam